Pernikahan dan Syarat Sah Talak - Abdul Hadi Ismail (Intiqad: Jurnal Agama dan Pendidikan Islam, 2019)
The word marriage comes Arabic namely nakaha and zawaja, and the meaning is to join and nakaha means marriage while aqad means agreement. So a marriage contract means a sacred agreement to bind yourself in marriage between men and women to form a happy family that is in accordance with Islamic law as devout moslims we will not be separated from Islamic law as a law that must obeyed by all moslims throughout the world.One of Islamic law is to regulate marriage, talak, divorce and refer to, these four things have been regulated in Islamic law, both in the quran and in the hadith. Marriage is an event that we often encounter in society even every day the Islamic community does marriage.